O caráter autônomo dos dêiticos sociais em missivas dos séculos XVIII a XX: um estudo em tradições discursivas - Colares, Ana Cátia Silva de Lemos (2021)
Studies in Textual Linguistics take u p some of Saussure's assumptions ([1916], 2003). Thus, as a conseque n c e of this Saussurean assumption and adopting the thought defended by Mondada and Dubois (2003), we believe that the categories created to describe th e world around us will change accordi ng to the statements, thus allowing us to conclude that the categori e s they are mutable and plural. Among these elements, which build the referential processes, the deictic referential relations stand out. Our general o bjective in this investigation is to characterize social deictics as an independent deictic category, ins t i tuted by panlinguistic aspects that reflect the hierarchical social relations in language, from the theoretical assumptions of Text Linguistics and D iscursive Traditions theory. In order to fulfill this objective, we rely on studies by Cavalcante (2000, 2 0 11, 2013), Ciulla (2002, 2008), Benveniste (1976), Lahud (1979), Lyons (1979), Filmore ([1984], 1997), Mondada and Dubois (1995), Apothéloz (2003), a mong others. Taking as reference the basic studies on Discursive Tradition, the works of Coseriu (1980, 2 0 0 6, 2007), Koch (1997, 2008), Oesterreicher (2001, 2008), Kabatek (2001, 2004, 200 5 ), among other researches will be considered. that take up the epis temological bases of DT. This researc h has an inductive character and is classified under the descriptive p oint of view, in addition, we inscribe this study in a mostly qualitative perspective. In order to prove the autonomy of the social deic, we analyzed 59 letters, of which 42 were of the official type, 12 of the letter to the editor/reader and 5 were clas s i fied as personal letters, all taken from a corpus with computerized access from the database. data from the Project for the History of Brazilian Port uguese (PHPB). Data collection was ca rried out in 2020 and evaluated 59 letters from the 18th, 19th and 2 0 t h centuries, comprising a time period of 259 years in total, divided into time periods of less than 35 years that intersperse two generations of each century. In conclusion, we can point out that social deicts establish processes of change and discursive p ermanence in speech acts that contribute to establish the people of discourse, pointing not only to the enunciator but also to the enunciatee, markin g the autonomy of the deictic field o f social deictics , in addition to power relations built over time a n d institutionalized by these deictics can contribute to the maintenance of a social hierarchy crystallized through language.